Music and Religious Education in Early Modern Europe - Kim, Hyun-Ah, author.
1 online resource (272 pages)
Keywords: Exploring the nexus of music and religious education involves fundamental questions regarding music itself, its nature, its interpretation, and its importance in relation to both education and the religious practices into which it is integrated. This cross-disciplinary volume of essays offers the first comprehensive set of studies to examine the role of music in educational and religious reform and the underlying notions of music in early modern Europe. It elucidates the context and manner in which music served as a means of religious teaching and learning during that time, thereby identifying the religio-cultural and intellectual foundations of early modern European musical phenomena and their significance for exploring the interplay of music and religious education today.